Point-of-care ultrasound with handheld devices in hematology: a monocentric single-stage phase II study. Issue 6 (12th May 2021) - Pagliuca, Simona; Bailly, Cecile; Talbot, Alexis; Bertinchamp, Rémi; Peyrony, Olivier; Elezi, Arben; Bourrier, Pierre; Lengline, Etienne
Abstract: Point of care ultrasound (PoCUS) with pocket-size devices is an efficient and safe imaging modality that became a standard of care in various clinical settings. However, its implementation in hematology has never been evaluated so far. We conducted a prospective monocentric study aiming to harvest data on its usage and to assess its diagnostic and interventional performance in improving the accuracy of basic physical examination in hematological patients. After a focused training program, six hematologists were trained and conducted this study. Sixty-two patients were included. Only in 19 cases, further specialized imaging was required, whereas, in 43 patients PoCUS was sufficient to address the clinical inquiries. The use of PoCUS devices was assessed for its performance difficulty and usefulness perception with satisfactory outcomes. This study represents a proof-of-concept application of PoCUS in hematology, suggesting benefits over the physical examination. KEY POINTS: PoCUS is particularly attractive in a hematological setting because able to improve the accuracy of physical examination. A hematology-focused training in PoCUS using handheld devices can allow hematologists to perform bed-side diagnostic and interventional US-based exams.